Generic diversity of the predaceous fungus gnats (Diptera: Keroplatidae) from Colombia - Jefferson Sauceda-Valderrama; Marta Wolff; Carolina Henao-Sepúlveda (Caldasia)
Keroplatidae is a family of Diptera that is poorly known and with scarce previous studies in Colombia, with only five species in four genera, and another five genera with non-identified species. This paper provides an extensive revision of the Keroplatidae from Colombia, with specimens collected along different altitudinal gradients, from Amazonian areas to Andean mountains. We found 17 genera, nine of these represent new records for Colombia (Cerotelion, Heteropterna, Placoceratias, Platyroptilon, Lapyruta, Micrapemon, Plautyra, Pyrtaula and Xenoplatyura). Additionally, the distribution in Colombia is extended for the genera Isoneuromyia, Keroplatus, Lyprauta, Macrocera, Neoceroplatus, Neoditomyia, Neoplatyura and Proceroplatus. For each genus we present a diagnosis, annotations of their biology based on literature and new field observations, and a distribution map.